SiC-based composite material runner insert structure in double-layer lithium-lead cooling device and optimization method of SiC-based composite material runner insert structure
By adopting the flow channel plug-in structure of SiC-based composite material with zirconia doped in the dual coolant lithium-lead device and performing finite element model optimization, the problem of low heat transfer efficiency of SiCf/SiC composite material is solved, and more efficient thermal insulation and structural stability are achieved.
Patent Information
- Application Number
- CN202411353149.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The heat transfer efficiency of the SiCf/SiC composite flow channel plug-in in the existing dual coolant lithium-lead device is not high, and the numerical simulation calculation accuracy is low, so it is impossible to accurately reflect the characteristics of the composite in different directions.
The SiC-based composite flow channel plug-in structure is adopted with zirconia doped, and the structural optimization is carried out through the finite element model to change the doping method of zirconia fibers to improve thermal insulation and structural stability.
The thermal insulation performance and structural stability of the SiC-based composite flow channel insert are significantly improved, the temperature difference between the inside and the outside reaches 340~395 degrees Celsius, and the maximum stress is reduced by 30~500MPa, which improves the accuracy during the design process and the reliability of the calculation results.
Smart Images

Figure CN119694603A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nuclear technology, and in particular relates to a SiC-based composite material flow channel plug-in structure in a double-layer lithium-lead cooling device and an optimization method thereof. Background Art
[0002] Nuclear fusion reactors are one of the important ways for humans to obtain clean energy in the future. Its basic principle is to combine light nuclei such as deuterium and tritium into heavier helium nuclei, releasing huge energy in the process. Compared with the currently widely used nuclear fission reactors, nuclear fusion reactors have obvious advantages. They have abundant fuel reserves, do not produce highly radioactive nuclear waste, and nuclear fusion reactions do not trigger chain reactions, so the risk of accidents is reduced.
[0003] However, there are many challenges in the commercial application of nuclear fusion reactions. In order to efficiently remove the heat generated by the reactor and recover tritium to maintain the nuclear fusion reaction, the concept of a dual-coolant lithium-lead device came into being. The device uses liquid lithium-lead as the main coolant and tritium breeder, and helium as the second coolant. The flow channel plug is a key component in the dual-coolant lithium-lead device, which is mainly used to solve the heat transfer and electromagnetic coupling problems between the liquid lithium-lead metal and the alloy layer. At present, the main material used for the flow channel plug is SiC. f / SiC composite materials.
[0004] To solve the problem of SiC f In order to solve the problem that the heat transfer efficiency of SiC composite materials is low, the present invention proposes to adopt a method of doping zirconia fibers to obtain a dual-coolant lithium-lead device design with thermal insulation performance.
[0005] Domestic and foreign research
[0006] In the field of nuclear engineering, the design of dual-coolant lithium-lead devices for nuclear fusion reactors is mostly focused on the use of SiC f / SiC composites are used as flow channel insert materials, but there is little research on zirconia fibers.
[0007] In the paper "Thermomechanical analysis of a Flow Channel Insert based on a SiC-sandwich material concept", the author Carlota Soto studied the thermomechanical properties of sandwich material flow channel inserts based on porous silicon carbide (SiC) core and dense silicon carbide outer layer in dual-cooled lithium-lead devices. Through finite element simulation methods, it was found that the maximum stress appeared in the dense SiC outer layer, and its stress magnitude was related to the thermal conductivity of the porous core and the thickness of the outer layer. In addition, the thickness and thermal conductivity of the porous SiC also directly affected the cooling effect of the dual-cooled lithium-lead device. However, the author used a variety of simplified models to approximate the porous silicon carbide core and the dense silicon carbide outer layer, resulting in a large deviation in the simulation results.
[0008] In the document "MAGNETOHYDRODYNAMIC AND THERMAL ISSUES OF THE SiC f / SiC FLOWCHANNEL INSERT》, the authors used numerical simulation methods to analyze SiC f The magnetohydrodynamic and thermal conductivity problems of SiC flow channel inserts were studied and the results showed that the best performance of SiC f / SiC FCI conductivity should be about 100S / m, thermal conductivity about 2W / m·K. This parameter configuration can strike a balance between minimizing the magnetohydrodynamic pressure drop and effectively managing heat conduction. However, although the article points out that three-dimensional effects such as temperature changes and convection may affect the performance of FCI, the article does not provide further advanced calculation models. In addition, the article does not provide any specific information on SiC f / SiC composite material simulation also uses an equivalent simplified model for simulation calculation, which cannot reflect the SiC f Different properties of / SiC composites in different directions.
[0009] In summary, the research on multilayer heterogeneous SiC in dual-coolant lithium-lead nuclear fusion devices at home and abroad f There are few studies on flow channel plugs of multilayer heterogeneous SiC composites, and in the calculation method of numerical simulation, equivalent simplified models are often used to simplify the problem, which is different from directly conducting multilayer heterogeneous SiC f In order to improve the accuracy and fidelity of the design process and the reliability of the calculation results, a multilayer heterogeneous SiC composite material was designed for a dual-coolant lithium-lead nuclear fusion device. f A design method for flow channel plugs of / SiC composite materials is very necessary. Summary of the invention
[0010] To solve the above problems, the purpose of the present invention is to provide a SiC-based composite material flow channel plug-in structure in a double-layer lithium-lead cooling device and an optimization method thereof. The structure and the optimization method thereof are mainly suitable for the structural design and structural optimization of the flow channel plug-in of a high-temperature liquid metal cooling device (double-layer lithium-lead cooling device) in a nuclear fusion reactor.
[0011] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0012] The invention discloses a SiC-based composite material flow channel plug-in structure in a double-layer lithium-lead cooling device. The structure is suitable for a high-temperature liquid metal cooling device in a nuclear fusion reactor, namely a double-layer lithium-lead cooling device. The structure has excellent thermal insulation and stability. The structure includes, from the inside to the outside, the following: a. a high-temperature PbLi liquid metal flow channel; b. a zirconia-doped SiC-based composite material; c. a liquid PbLi isolation layer; d. a steel structure alloy layer; and e. a helium cooling channel.
[0013] 2. The flow channel plug structure optimization method mainly includes the following steps: a. Determine the above-mentioned related structural size parameters; b. Construct a finite element model of the SiC-based composite material flow channel plug; c. Set the thermal and mechanical parameters of the structure and set related boundary conditions; d. Change the zirconia fiber doping method and perform calculations; e. Analyze the simulation results, process the relevant data to obtain the optimization value, and compare the optimization value to obtain the optimal structural design.
[0014] Compared with the prior art, the present invention has the following advantages:
[0015] 1. The SiC-based composite material flow channel plug-in in the double-layer lithium-lead cooling device doped with zirconium oxide developed by the present invention can efficiently improve the temperature difference between the innermost high-temperature PbLi liquid metal flow channel and the outermost alloy surface. Based on different zirconium oxide doping methods, the temperature difference between the inside and outside of the SiC-based composite material flow channel plug-in reaches 340 to 395 degrees Celsius.
[0016] 2. The SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device doped with zirconium oxide developed by the present invention can efficiently improve the structural stability. Compared with the SiC-based composite material flow channel plug without zirconium oxide doping, the maximum structural stress of the SiC-based composite material flow channel plug doped with zirconium oxide is reduced by 30 to 500 MPa.
[0017] 3. The zirconium oxide-doped SiC-based composite material flow channel plug structure developed by the present invention has a more concentrated cross-sectional isotherm distribution compared to the SiC-based composite material flow channel plug without zirconium oxide doping.
[0018] 4. The optimization method of the SiC-based composite material flow channel plug-in in the double-layer lithium-lead cooling device developed by the present invention realizes the simulation of SiC fiber-reinforced composite materials. Compared with the equivalent simplified model commonly used at present, the design method used in the present invention has the advantages of high accuracy and reliability because it realizes the complete modeling and simulation calculation of the composite material matrix and fiber.
[0019] 5. The optimization method of the SiC-based composite material flow channel plug-in in the double-layer lithium-lead cooling device developed by the present invention has high efficiency. It only needs to change the parameters according to the actual working conditions to quickly perform calculations and designs. It has high efficiency and strong applicability.
[0020] 6. The optimization method of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device developed by the present invention has a high degree of freedom. When used, the weight coefficients α and β can be modified according to actual needs to achieve structural screening of materials with different performances. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a structural diagram of the SiC-based composite material flow channel plug-in in a double-layer lithium-lead cooling device, in which the zirconia fiber doping method is 2 or 3 layers of long fiber doping.
[0022] Figure 2 The figure is a flow chart of the optimization method of the present invention.
[0023] Figure 3 Comparison of optimized quantities of SiC-based composite material flow channel inserts in double-layer lithium-lead cooling devices with different zirconia fiber doping methods.
[0024] Figure 4 The isotherm simulation results of the cross-section of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device are shown in Figure 2. Figure 4 (a) is the simulation result of the undoped zirconia fiber model. Figure 4 (b) shows the simulation results of the zirconia continuum model doped in the 2nd and 3rd layers of SiC fibers.
[0025] Figure 5 These are the simulation results of the maximum stress and average surface temperature of the SiC-based composite material flow channel plug-in structure of the zirconia continuum doped in the 2nd and 3rd layers of SiC fibers and the SiC-based composite material flow channel plug-in structure without zirconia doping. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0027] like Figure 1As shown in the figure, the SiC-based composite material flow channel plug structure in the double-layer lithium-lead cooling device of the present invention includes, from the inside to the outside in sequence: a. High-temperature PbLi liquid metal flow channel; b. Zirconia-doped SiC-based composite material; c. Liquid PbLi isolation layer; d. Steel structure alloy layer; e. Helium cooling channel.
[0028] Among them, the SiC-based composite material is composed of n layers of SiC fibers and a SiC matrix filled in the voids of the SiC fibers. The zirconia doping position is the i-th layer, and 1 < i ≤ n. The zirconia doping methods in the i-th layer include: a. Zirconia long fiber doping; b. Zirconia short fiber doping; c. Zirconia continuum doping.
[0029] The function of the liquid PbLi isolation layer is to adapt to different thermal expansions, reduce heat conduction, and prevent corrosion, thereby protecting the structural integrity of the steel structure alloy layer.
[0030] There are multiple helium cooling channels, which are distributed in the steel structure alloy layer.
[0031] Compared with the SiC-based composite material flow channel plug without zirconia doping, the cross-sectional isotherm distribution of the SiC-based composite material flow channel plug with zirconia doping used in the present invention is more concentrated; based on different zirconia doping methods, the temperature difference between the inside and outside of the SiC-based composite material flow channel plug reaches 340 - 395 degrees Celsius; compared with the SiC-based composite material flow channel plug without zirconia doping, the maximum stress of the structure using the SiC-based composite material flow channel plug with zirconia doping is reduced by 30 - 500 MPa; the above data show that this structure has excellent thermal insulation and stability.
[0032] The optimization method of the SiC-based composite material flow channel plug structure in the double-layer lithium-lead cooling device of the present invention can efficiently realize the fluid-solid coupling heat transfer and thermodynamic simulation of the SiC-based composite material flow channel plug and conduct structural optimization; as Figure 2 shown, the specific steps are as follows:
[0033] Step 1:
[0034] Determine the relevant structural parameters of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device, which are, in the order from the inside to the outside of the structure:
[0035] Structure 1: High-temperature PbLi liquid metal flow channel: Set the size of the high-temperature PbLi liquid metal flow channel to 20 mm × 20 mm;
[0036] Structure 2: Zirconia-doped SiC-based composite material: Set the zirconia doping methods of long fiber doping and continuum doping, the total thickness of the SiC-based composite material to 5 mm, the number of fiber layers to 5 layers, the fiber cross-sectional shape to oval, and the fiber cross-sectional size to 0.06 mm × 0.012 mm;
[0037] Structure 3: Liquid PbLi isolation layer: Set the thickness of the liquid PbLi isolation layer to 0 mm;
[0038] Structure 4: Steel structure alloy layer: The steel structure alloy layer is composed of steel structure, and the steel thickness in the steel structure is set to 10mm;
[0039] Structure 5: Helium cooling channel: The size of the helium cooling channel is set to 5mm×5mm, the number is 24, and it is distributed in the alloy layer of the steel structure;
[0040] Step 2:
[0041] In the modeling software, the structure is modeled from the inside to the outside and a finite element model with internal boundaries is formed; according to the relevant structural parameters in step 1, the specific modeling steps are as follows:
[0042] Structure 1: The high-temperature PbLi liquid metal flow channel is modeled by stretching;
[0043] Structure 2: The zirconia-doped SiC-based composite material uses sweeping and arraying methods to establish a two-dimensional braided model. The specific methods are as follows: a. Determine the sweep path using a spline curve based on relevant dimensional data; b. Draw the SiC fiber cross section at the end point of the sweep path; c. Select the SiC fiber cross section and the sweep path to model a single SiC fiber to obtain a single SiC fiber model; d. Use a circular array method to rotate the single SiC fiber model 180° to construct adjacent SiC fiber bundles; e. Use a linear array method to replicate the SiC fiber bundle to construct the lateral SiC fibers within the layer; f. Use a spline curve to draw a longitudinal SiC fiber sweep path, and repeat the above steps b, c, d, and e to construct the longitudinal SiC fibers in the layer; g. Repeat the above steps a, b, c, d, e, and f to construct multilayer SiC fibers according to the number of SiC fiber layers required; h. Use a SiC matrix to fill the gaps between the SiC fibers, wherein the SiC matrix is modeled using a stretching method, and the interface between the SiC matrix and the SiC fiber and the interface between the SiC matrix and the high-temperature PbLi liquid metal flow channel are retained during the modeling process; i. Model the zirconia fiber according to the zirconia doping method set in step 1;
[0044] Structure 3: The liquid PbLi isolation layer is modeled by stretching, and the interface between the liquid PbLi isolation layer and the SiC substrate is retained during the modeling process;
[0045] Structure 4: The steel structure alloy layer is modeled by stretching, and the interface between the steel structure alloy layer and the liquid PbLi isolation layer is retained during the modeling process;
[0046] Structure 5: The helium cooling channel is modeled by stretching, and the interface between the helium cooling channel and the steel structure alloy layer is retained during the modeling process;
[0047] Step 3:
[0048] Import the finite element model with internal boundaries into the finite element software, add the fluid-solid coupling heat transfer module and the thermal expansion module, set the thermodynamic and heat transfer material properties related to SiC fiber, SiC matrix, zirconia fiber and steel structure, set the inlet and outlet of the high-temperature PbLi liquid metal flow channel, liquid PbLi isolation layer and helium cooling channel, and set the fluid flow rate and inlet temperature; in addition, specify the material curve coordinate system along the SiC fiber direction;
[0049] Step 4: Change the doping position, doping method and number of layers of zirconia fiber, calculate and obtain simulation results of different models. The specific operation method is: change the relevant material properties and material coordinate system of zirconia fiber and SiC matrix at the corresponding position, without directly changing the finite element model containing internal boundaries;
[0050] Step 5: Compare the simulation results of the SiC-based composite material flow channel plug in the above-mentioned double-layer lithium-lead cooling device doped with zirconia with the simulation results of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device without zirconia, analyze the temperature difference on both sides of the flow channel plug, the maximum stress of the structure and the average stress between the fibers of each layer, and obtain the optimal structural design; the specific method is as follows: The average surface temperature of the outermost layer of the steel structure alloy layer of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device doped with zirconia is T 1 , the average interface temperature between the nth layer of fibers is The maximum interface temperature between the nth layer of fibers is The maximum stress of the flow channel plug structure is σ 1 , the maximum stress at the interface between the nth layer of fibers is The average stress at the interface between the nth layer of fibers is: where i∈[1,n-1]; the average surface temperature of the outermost layer of the steel structure alloy layer of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device without zirconia is T 1,x , the average interface temperature between the nth layer of fibers is The maximum interface temperature between the nth layer of fibers is The maximum stress of the flow channel plug structure is σ 1,x , the maximum stress at the interface between the nth layer of fibers is The average stress at the interface between the nth layer of fibers is: Where i∈[1,n-1], the optimization amount γ is calculated using the following formula:
[0051]
[0052] Among them, α and β are weight coefficients, which are defined according to the requirements; is the temperature optimization quantity, reflecting the optimization quantity of the thermal insulation performance of the structure; θ is the stress optimization quantity, reflecting the optimization quantity of the structural stability.
[0053] By comparing the size of the optimization amount γ, the optimization amount of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device with different doping methods, doping positions and layers is compared to determine the optimal structure. max When , the corresponding structure is the optimal structure.
[0054] like Figure 3 As shown, the ordinate indicates the optimization amount of different fiber doping methods. By comparison, it is found that the optimization amount of the model simulation results using 2 and 3 layers of continuum doping is much higher than other doping methods, indicating that the SiC-based composite material flow channel plug-in doped with zirconia continuum in the 2nd and 3rd layers of SiC fibers is the optimal structure.
[0055] Figure 4 (b) is the cross-sectional isotherm simulation result of the SiC-based composite material flow channel plug structure with zirconia continuum doping in the second and third layers of SiC fibers. The temperature difference between the innermost high-temperature PbLi liquid metal flow channel and the outermost steel structure alloy surface reaches 340 degrees Celsius, which is comparable to Figure 4 The isothermal simulation results of the cross-section of the flow channel plug structure of the SiC-based composite material without zirconia doping shown in (a) show that its isothermal distribution is more dense, indicating that its thermal insulation performance is better.
[0056] Figure 5 The simulation results of the maximum stress and surface average temperature of the SiC-based composite material flow channel plug-in doped with zirconia continuum in the 2nd and 3rd layers of SiC fibers and the SiC-based composite material flow channel plug-in without zirconia doping are shown. The results show that the maximum stress is reduced by 500MPa and the average surface temperature is reduced by 54℃, indicating that the stability and reliability of the structure are significantly improved.
Claims
1. A SiC-based composite material flow channel plug-in structure in a double-layer lithium-lead cooling device, characterized in that: This structure is applicable to the high-temperature liquid metal cooling device in a fusion reactor, namely the double-layer lithium-lead cooling device. This structure has excellent thermal insulation and stability. From the inside to the outside, it successively includes: Structure 1: High-temperature PbLi liquid metal flow channel; Structure 2: Zirconia-doped SiC-based composite material. The SiC-based composite material consists of n layers of SiC fibers and a SiC matrix filled in the voids of the SiC fibers. The zirconia doping position is the i-th layer, and 1 < i ≤ n. The zirconia doping methods in the i-th layer include: a. Long zirconia fiber doping; b. Short zirconia fiber doping; c. Zirconia continuum doping; Structure 3: Liquid PbLi isolation layer. The function of the liquid PbLi isolation layer is to adapt to different thermal expansions, reduce heat conduction, and prevent corrosion, thereby protecting the structural integrity of the steel structure alloy layer; Structure 4: Steel structure alloy layer; Structure 5: Helium cooling channels. There are multiple helium cooling channels distributed in the steel structure alloy layer.
2. The SiC-based composite material flow channel plug-in structure in the double-layer lithium-lead cooling device according to claim 1, characterized in that: a. Compared with the SiC-based composite material flow channel plug structure without zirconia doping, the cross-sectional isotherm distribution of the zirconia-doped SiC-based composite material flow channel plug is more concentrated; b. Based on different zirconia doping methods, the temperature difference between the inside and outside of the SiC-based composite material flow channel plug reaches 340 - 395 degrees Celsius; c. Compared with the SiC-based composite material flow channel plug structure without zirconia doping, the maximum stress of the structure of the zirconia-doped SiC-based composite material flow channel plug is reduced by 30 - 500 MPa. The above data indicate that this structure has excellent thermal insulation and stability.
3. The optimization method for the SiC-based composite material flow channel plug structure in the double-layer lithium-lead cooling device according to any one of claims 1 to 2. This method can efficiently realize the fluid-solid coupling heat transfer and thermodynamic simulation of the SiC-based composite material flow channel plug and perform structural optimization; the specific steps are as follows: Step 1: Determine the relevant structural parameters of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device. In the order from the inside to the outside of the structure, they are: Structure 1: High-temperature PbLi liquid metal flow channel: Set the size of the high-temperature PbLi liquid metal flow channel; Structure 2: Zirconia-doped SiC-based composite material: setting the zirconia doping method, the overall thickness of the SiC-based composite material, the number of SiC fiber layers, and the cross-sectional shape and size of the SiC fiber; Among them, the doping methods include: long zirconia fiber doping, short zirconia fiber doping, and zirconia continuum doping; Structure 3: Liquid PbLi isolation layer: Set the thickness of the liquid PbLi isolation layer; Structure 4: Steel structure alloy layer: The steel structure alloy layer is composed of a steel structure, and the thickness of the steel in the steel structure needs to be set; Structure 5: Helium cooling channels: The helium cooling channels are distributed in the steel structure alloy layer, and the size and quantity of the helium cooling channels need to be set; Step 2: In the modeling software, model in the order from the inside to the outside of the structure and form a finite element model containing internal boundaries; According to the relevant structural parameters in Step 1, the specific modeling steps are as follows: Structure 1: The high-temperature PbLi liquid metal flow channel is modeled by the stretching method; Structure 2: The zirconia-doped SiC-based composite material uses sweeping and arraying methods to establish a two-dimensional braided model. The specific methods are as follows: a. Determine the sweep path using a spline curve based on relevant dimensional data; b. Draw the SiC fiber cross section at the end point of the sweep path; c. Select the SiC fiber cross section and the sweep path to model a single SiC fiber to obtain a single SiC fiber model; d. Use a circular array method to rotate the single SiC fiber model 180° to construct adjacent SiC fiber bundles; e. Use a linear array method to replicate the SiC fiber bundle to construct the lateral SiC fibers within the layer; f. Use a spline curve to draw a longitudinal SiC fiber sweep path, and repeat the above steps b, c, d, and e to construct the longitudinal SiC fibers in the layer; g. Repeat the above steps a, b, c, d, e, and f to construct multilayer SiC fibers according to the number of SiC fiber layers required; h. Use a SiC matrix to fill the gaps between the SiC fibers, wherein the SiC matrix is modeled using a stretching method, and the interface between the SiC matrix and the SiC fiber and the interface between the SiC matrix and the high-temperature PbLi liquid metal flow channel are retained during the modeling process; i. Model the zirconia fiber according to the zirconia doping method set in step 1; Structure 3: The liquid PbLi isolation layer is modeled by stretching, and the interface between the liquid PbLi isolation layer and the SiC substrate is retained during the modeling process; Structure 4: The steel structure alloy layer is modeled by stretching, and the interface between the steel structure alloy layer and the liquid PbLi isolation layer is retained during the modeling process; Structure 5: The helium cooling channel is modeled by stretching, and the interface between the helium cooling channel and the steel structure alloy layer is retained during the modeling process; Step 3: Import the finite element model with internal boundaries into the finite element software, add the fluid-solid coupling heat transfer module and the thermal expansion module, set the thermodynamic and heat transfer material properties related to SiC fiber, SiC matrix, zirconia fiber and steel structure, set the inlet and outlet of the high-temperature PbLi liquid metal flow channel, liquid PbLi isolation layer and helium cooling channel, and set the fluid flow rate and inlet temperature; in addition, specify the material curve coordinate system along the SiC fiber direction; Step 4: Change the doping position, doping method and number of layers of zirconia fiber, calculate and obtain simulation results of different models. The specific operation method is: change the relevant material properties and material coordinate system of zirconia fiber and SiC matrix at the corresponding position, without directly changing the finite element model containing internal boundaries; Step 5: Compare the simulation results of the SiC-based composite material flow channel plug in the above-mentioned double-layer lithium-lead cooling device doped with zirconia with the simulation results of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device without zirconia, analyze the temperature difference on both sides of the flow channel plug, the maximum structural stress and the average stress between each layer of fibers, and obtain the optimal structural design; the specific method is as follows: the average surface temperature of the outermost layer of the steel structure alloy layer of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device doped with zirconia is T1, and the average interface temperature between the nth layer of fibers is The maximum interface temperature between the nth layer of fibers is The maximum stress of the flow channel plug structure is σ1, and the maximum stress of the interface between the nth layer of fibers is The average interface stress between the nth layer of SiC fibers is: where i∈[1,n-1]; the average surface temperature of the outermost layer of the steel structure alloy layer of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device without zirconia is T 1,x , the average interface temperature between the nth layer of fibers is The maximum interface temperature between the nth layer of fibers is The maximum stress of the flow channel plug structure is σ 1,x , the maximum stress at the interface between the nth layer of fibers is The average stress at the interface between the nth layer of fibers is: Where i∈[1,n-1], the optimization amount γ is calculated using the following formula: Among them, α and β are weight coefficients, which are defined according to the requirements; is the temperature optimization quantity, reflecting the optimization quantity of the thermal insulation performance of the structure; θ is the stress optimization quantity, reflecting the optimization quantity of the structural stability; By comparing the size of the optimization amount γ, the optimization amount of the SiC-based composite material flow channel plug in the double-layer lithium-lead cooling device with different doping methods, doping positions and layers is compared to determine the optimal structure. max When , the corresponding structure is the optimal structure.
Citation Information
Patent Citations
Beryllium-based liquid cladding layer based on silicon carbide tube
CN111863286A
Supercritical carbon dioxide liquid lithium lead double-cooling cladding
CN113593727A
Method for predicting residual stiffness of ceramic matrix woven composite material in thermal oxygen environment
CN118098454A
SiC cladding multi-objective optimization design method based on genetic algorithm
CN118410711A
Nuclear fusion reactor
JP1990309288A
Cited By
Liquid lithium lead self-cooling cladding with low MHD pressure drop
CN120674109A